“Keraton’s Culinary”: Strategi Edukasi Budaya Melalui Board Game Augmented Reality Bagi Gen Z Yogyakarta - Santana, Romario; Hendrawan, Freddy; Dewi, Ni Made Emmi Nutrisia; Dinata, Ramanda Dimas Surya (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
The rapid development of technology and intense exchange of information has caused the younger generation to be easily influenced by outside cultures. This has resulted in the traditional food of Kraton Yogyakarta, which is full of philosophy and deep cultural values, is threatened to be forgotten by the current generation, especially Generation Z in Yogyakarta. The purpose of this research and design is to focus on efforts to preserve traditional food through board game media integrated with Augmented Reality technology to educate the importance of traditional cuisine as a regional cultural identity. The design method uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model, which consists of needs analysis, game conceptual design, prototype development, trial implementation, and effectiveness evaluation. This method was chosen because it provides a systematic structure in designing an effective gaming experience. The results of the study indicate that there is a crisis of knowledge regarding traditional culinary culture among Generation Z in Yogyakarta, caused by a lack of media that presents such content in a visually appealing and technologically relevant manner. The design results show that board games with Augmented Reality technology can create an interactive and immersive educational experience and increase Generation Z's understanding of the food philosophy of the Yogyakarta Palace. This research and design is expected to contribute to the development of interactive, immersive, and sustainable educational media.